Nonequilibrium Hanbury Brown-Twiss interferometry: Theory and application to binary stars - Adrian E. Rubio López; Ashwin K. Boddeti; Fanglin Bao; Hyunsoo Choi; Zubin Jacob (Physical Review Research, 2023)
Intensity interferometry based on Hanbury Brown and Twiss's seminal experiment for determining the radius of the star Sirius formed the basis for developing the quantum theory of light. To date, the principle of this experiment is used in various forms across different fields of quantum optics, imaging, and astronomy. Although the technique is powerful, it has not been generalized for objects at different temperatures. Here, we address this problem using a generating functional formalism by employing the P-function representation of quantum-thermal light. Specifically, we investigate the photon coincidences of a system of two extended objects at different temperatures using this theoretical framework. We show two unique aspects in the second-order quantum coherence function: interference oscillations and a long-baseline asymptotic value that depends on the observation frequency, temperatures, and size of both objects. We apply our approach to the case of binary stars and discuss the advantages of measuring these two features in an experiment. In addition to the estimation of the radii of each star and the distance between them, we also show that the present approach is suitable for the estimation of temperatures as well. To this end, we apply it to the practical case of binary stars Luhman 16 and Spica α Vir. We find that for currently available telescopes, an experimental demonstration is feasible in the near term. Our work contributes to the fundamental understanding of intensity interferometry of quantum-thermal light and can be used as a tool for studying two-body thermal emitters, from binary stars to extended objects.